Evaluation of Variation in Nursery Pig Growth Performance Utilizing Different Allotment Strategies - Abigail K. Jenkins; Jordan T. Gebhardt; Jason C. Woodworth; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 360 pigs (200 × 400 DNA) were used in a 43-d nursery trial (initially 12.4 ± 0.37 lb) to evaluate multiple strategies for allotting pigs to pens in swine research trials. At placement, the population was split into 3 cohorts with similar average weight and standard deviation. Each cohort was randomly assigned to 1 of 3 allotment strategies. Strategy 1 (random) utilized a simple randomization strategy with each pig randomized to pen independent of all other pigs. Strategy 2 [body weight (BW) distribution] sorted each pig within the cohort into 1 of 5 BW groups. One pig from each weight group was then randomly assigned to pen such that distribution of BW within pen was uniform across pens. Strategy 3 (BW grouping) sorted pigs within the cohort into 3 BW categories: light, medium, and heavy. Within each BW category, pigs were randomly assigned to pen to create pens of pigs from each BW category. There were 72 pens in the trial with 5 pigs per pen and 24 pens per allotment strategy. For all strategies, once pigs were allotted to pens, pens were allotted to 1 of 2 treatments for a concurrent trial. Treatment diets consisted of basal levels of Zn and Cu from the trace mineral premix for the duration of the study (110 and 17 mg/kg, respectively; NC), or diets (PC) with carbadox (50 g/ton; Mecadox, Phibro Animal Health, Teaneck, NJ) fed in phase 1 and 2, pharmacological levels of Zn and Cu (2,414 mg/kg Zn from ZnO; 168 mg/kg Cu from CuSO4) in phase 1 and only Cu (168 mg/kg Cu from CuSO4) in phase 2. There were no allotment × treatment interactions (P>0.10). Pigs fed the PC diet had improved (P<0.001) ADG, ADFI, F/G, and final BW compared to pigs fed the NC diet. The coefficients of variation (CV) within pen between all pens on each allotment strategy and for the entire population of each allotment strategy were calculated. For between-pen and within-pen CV, pigs allotted using the BW grouping strategy had the lowest CV at allotment and final weigh day. Results were used to estimate the replication required with each allotment strategy to obtain significant differences with different percentage responses. Fewer replications are required to discern significant differences in ADG and final BW when allotting pigs utilizing BW grouping. However, there is no meaningful difference between allotment strategies in the replications required to detect significant differences for overall feed efficiency. When conducting nursery research with pen serving as the experimental unit, the data of this trial would support that a BW grouping allotment strategy would produce the least within-pen and pen-to-pen variation.
Keywords: allotment strategy; body weight variation; nursery pig